Analisa Usahatani Pembibitan Cabai Merah (Capsicum Annum L.): Studi Kasus di Desa Badang Kecamatan Ngoro Kabupaten Jombang - Sri Nugrahani (Universitas Darul Ulum, 2015)
This research aims to assess the efficiency, profitability and break event point of farm breeding of red chilli in the village Badang. The method of selecting the study area was purposively (intentionally), with consideration of the area is a breeding area farmers in the district centers Jombang. Even though central areas, farmers breeding population in the study area amounted to 47 people. Because less than 100 people, the respondents taken all of the population. The results showed that the total costs incurred for one-time production of red chilli seeds is Rp 7,689,620.51 with an average yield of seed grain 75361.70. The average farmer breeders sell their produce at a price of Rp 200 per seed. Then the average receipts for one production per farm is Rp 15 072 340. From the results of red chili breeding farm in one of this production, then the average gains are Rp7.382.719,49 per farm. Rates of return of red chili breeding farm amounted to 96.01%. Cultivation of red chilli in the village nursery Badang worth the effort to level the feasibility of 1.96. Value the rupiah BEP is 102.04, while 38.44 product can be said that the BEP rupiah and products have achieved so farms breeding red chili worth the effort. In this research, red chili breeding farm income benefit approach, that is assuming all seed production sold out.